2022
DOI: 10.1177/20414196221096699
|View full text |Cite
|
Sign up to set email alerts
|

Application of transfer learning for the prediction of blast impulse

Abstract: Transfer learning offers the potential to increase the utility of obtained data and improve predictive model performance in a new domain, particularly useful in an environment where data is expensive to obtain such as in a blast engineering context. A successful application in this respect will improve existing surrogate modelling approaches to allow for holistic and efficient strategies to protect people and structures subjected to the effects of an explosion. This paper presents a novel application of transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Nevertheless, the ANN was shown to be able to predict the roof loads on the building within a fraction of a second, making it a promising technique for future fast-running codes. Recently, the use of ANNs for confined loading (Dennis et al, 2020) and for near-field loading (Pannell et al, 2021(Pannell et al, , 2022a(Pannell et al, , 2022b were also successfully demonstrated.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Nevertheless, the ANN was shown to be able to predict the roof loads on the building within a fraction of a second, making it a promising technique for future fast-running codes. Recently, the use of ANNs for confined loading (Dennis et al, 2020) and for near-field loading (Pannell et al, 2021(Pannell et al, , 2022a(Pannell et al, , 2022b were also successfully demonstrated.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Likewise, Ruscade et al [111] use data-rich experimental work (30 pressure vs. time data sets per test) for the training of a numerical model, although no further detail is provided about the model. Other blast-related applications of data-driven [112,113] and neural network-based predictive approaches [114][115][116] have been shown to have highly favourable computa-tional times compared to CFD simulations. Flood et al [117] showcased a neural network that was capable of running as much as six orders of magnitude faster than a CFD simulation for a 3D scenario, with similar results reported by Kang and Park [118].…”
Section: Neural Networkmentioning
confidence: 99%
“…Recently, Dennis et al (2021) successfully developed a rapid artificial neural network (ANN) model to predict the blast loading in a confined internal environment. Pannell et al (2022a; 2022b) utilised ANNs to explore physics-guided regularisation and transfer learning respectively to improve the ability of an ANN to predict near-field blast loading. Another ANN methodology to model non-linear blast loading behind a blast barrier protective wall was developed by Bewick et al (2011).…”
Section: Literature Review and Theoretical Considerationsmentioning
confidence: 99%
“…This interaction has been investigated in the literature along two different lines: (i) the initial interaction between an obstacle and the blast wave to predict the frontal load, and (ii) to understand the consequences of the wave interaction in the downstream region. To predict such a load, ANN methods have successfully demonstrated the ability to estimate complex blast loads in scenarios such as a confined environment (Dennis et al, 2021), near-field blast loading (Pannell et al, 2022a; 2022b; Holgado et al, 2022) and for a target protected by a solid wall (Bewick et al, 2011). However, there is no deep insight into the characterization of blast wave interaction with a cylindrical obstacle and its role in mitigating the load acting on shadowed structural rigid targets.…”
Section: Introductionmentioning
confidence: 99%